The Role of Tour Guides in Enhancing Tourist Experience and Satisfaction at Taman Mini Indonesia Indah Jakarta - Pusparani, Pusparani; Rachman, Arief Faizal; Hutagalung, M. Husen; Boediman, Surya Fadjar; Enggriani, Mimi (Jurnal Penelitian Pariwisata, 2025)
This study aims to analyze the impact of tour guides' interpersonal communication on tourists' experiences at Taman Mini Indonesia Indah (TMII), with tourist satisfaction as a moderating variable. The research uses a quantitative method with a descriptive and causal design. Data was collected through questionnaires distributed to 200 tourists visiting TMII who were directly involved in guided tours. The data analysis technique used is Smart PLS to test the relationships between variables. The results show that interpersonal communication of tour guides has a positive and significant effect on tourists' experiences, and tourist satisfaction serves as a moderating variable that strengthens this relationship. Open, friendly, and clear communication from the tour guide can enhance tourist satisfaction, which in turn improves tourists' experiences. This study concludes that the quality of communication between tour guides and tourists plays a crucial role in creating a memorable and satisfying tourism experience. Recommendations for TMII management include placing more emphasis on interpersonal communication training for tour guides and optimizing the system for measuring tourist satisfaction. Tour guides are encouraged to continuously improve their communication skills, while tourists are advised to actively participate in interactions with tour guides for a more enriching tourism experience. Keywords: Interpersonal communication, tourist satisfaction, tourist experience, tour guide